Production of a high purity, C‐tagged hepatitis B surface antigen fusion protein VLP vaccine for malaria expressed in Pichia pastoris under cGMP conditions. Issue 10 (22nd July 2022) - Mukhopadhyay, Ekta; Brod, Florian; Angell‐Manning, Philip; Green, Nicola; Tarrant, Richard D.; Detmers, Frank J.; Bolam, Emma J.; Baleanu, Ioana N.; Hobson, Mark; Whale, Gary; Morris, Susan J.; Ashfield, Rebecca; et al.
Abstract: Virus‐like particles (VLPs) induce strong humoral and cellular responses and have formed the basis of some currently licensed vaccines. Here, we present the method used for the production of R21, a VLP‐based anti‐sporozoite malaria vaccine, under current Clinical Good Manufacturing Practice regulations (cGMP). Previous preclinical studies in BALB/c mice showed that R21 produced almost complete protection against sporozoite challenge with transgenic Plasmodium berghei parasites. Here, we have modified the preclinical production process to enable the production of sufficient quantities of highly pure, clinical‐grade material for use in human clinical trials. The R21 construct was re‐engineered to include a C‐tag to allow affinity‐based separation from the major contaminant alcohol oxidase 1 (AOX 1, ~74 kDa). To our knowledge, this is the first use of C‐tag technology to purify a VLP vaccine candidate for use in human clinical trials. The R21 vaccine has shown high‐level efficacy in an African Phase IIb trial, and multiple clinical trials are underway to assess the safety and efficacy of the vaccine. Our findings support the future use of C‐tag platform technologies to enable cGMP‐compliant biomanufacturing of high purity yeast‐expressed VLP‐based vaccines for early phase clinical trials when clinical grade material is required in smaller quantities in a quick time frame.